2016
DOI: 10.1186/s40173-016-0074-9
|View full text |Cite
|
Sign up to set email alerts
|

Sharing housework between husbands and wives: how to improve marital satisfaction for working wives in Japan

Abstract: This paper examines whether and how the marital satisfaction of Japanese couples is related to the housework the spouse performs. For single-earner couples, both husbands and wives are more satisfied with the other spouse if the wife performs the greater share of the housework on weekdays. In dual-earner couples, both husbands and wives experience higher spousal satisfaction when the other spouse performs more housework on weekdays. Japanese dual-earner couples are unable to spend more time on housework, becau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
0
10
0
1
Order By: Relevance
“…Lack of emotional support from a partner is also closely related to anxiety during the pregnancy or postnatal period 36 . In families where responsibilities are shared, spouses and partners have a more positive view of family life, have improved partner relationships, and higher levels of marital satisfaction 37 . The situation for single mothers is quite different, and the sole responsibility of caring for a baby may cause depression and anxiety disorders which may have a negative effect on maternal attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of emotional support from a partner is also closely related to anxiety during the pregnancy or postnatal period 36 . In families where responsibilities are shared, spouses and partners have a more positive view of family life, have improved partner relationships, and higher levels of marital satisfaction 37 . The situation for single mothers is quite different, and the sole responsibility of caring for a baby may cause depression and anxiety disorders which may have a negative effect on maternal attachment.…”
Section: Discussionmentioning
confidence: 99%
“…Since men in heterosexual marriages are more likely to be affected by spousal social control, 37 the absence of a spouse may increase unhealthy behaviors especially in men. Although Japan is a country in which traditional familism is valued, and housework and meal preparation are overwhelmingly performed by women, 20,21 the effects of marital transitions on vegetable intake may show similar trends across cultures. Further studies are needed to elucidate gender differences in the effects of marital transitions on dietary habits.…”
Section: A C C E P T E D V E R S I O Nmentioning
confidence: 99%
“…Because of the historical and cultural background of familism and gender specialization in East Asian societies, there is an expectation that women, more so than men, will perform household tasks, including food preparation. 20,21 Thus, marital transitions may have a different impact on men and women in East Asia than in Western countries because of cultural differences in gender specialization. For example, the traditional dietary pattern in Japan is composed of high consumption of soybean products, fish, vegetables, and green tea.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, those women who never performed intermittent work (e.g., repairs) had the best relationship quality. Recently, a study by Kobayashi et al (2016) of more than 4,000 Japanese married women and men, confirmed that the women took on more housework than their husbands. They also found that spousal satisfaction of dual-earner couples increased as the share of housework performed on the weekdays by the other spouse increased, but this relationship was stronger among the women.…”
Section: Housework Division Between Partners and Marital Outcomesmentioning
confidence: 99%